Analysis of Student's Beginning Reasoning Ability In Pisa-Like-Based Mathematics Problem Solving - Ryan Ananda Nolly; Rohwandi Rohwandi; Nur Annisa Husna; Jeremia Manurung; Razid Ananda Siregar; Andrea Arifsyah Nasution (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
The research carried out in this article is a descriptive type of research to know the level of reasoning ability and analysis of the initial capacity in solving math problems of students in SDS Prestige Bilingual School on Minimum Competency Assessment and Non-Minimum Competency Assessment PISA like math-based questions. The subjects in this study were third-grade students of SDS Prestige Bilingual School for the 2021/2022 academic year, with a total of 14 students. The data collection method used in this study was to first distribute pretest questions to students with 60 minutes of processing time and continue with interviews. Interviews are intended to dig for more profound information about how students solve the given problems. The results of the pretest and interviews will be used as the primary data in answering the research problems. Based on the results of the research that has been carried out, it is obtained data that the research findings show students' initial reasoning abilities in general, students can solve the questions in the problem. In solving the questions given, some students tended to do trial and error, while the rest answered with good performance with answers that matched expectations. Keywords: Initial understanding, PISA, Reasoning ability, Minimum Competency Assessment.